"Gypsies, Tramps & Thieves": Examining Representations of Roma Culture in 70 Years of American Television. (December 2017) - Schneeweis, Adina; Foss, Katherine A.
Most Americans know little about the "Gypsies, " or Roma, other than what they learn in the media. Although research shows that media have perpetuated stereotypes, there is thin anthological attention to the representation of Gypsies in American media. This study examines portrayals of Gypsies in fictional and reality television programs 1953-2014, and reveals that American television has reinforced stereotypes, suggesting that Gypsies are consistently different, a closed ethnic community resistant to change. More recent representations convey that Gypsies may be misunderstood due to their cultural history, yet this considerably less visible depiction emerges as a mere nod toward tolerance.